Deteksi Fluktuasi Harga Saham di Lima Negara ASEAN - Dewi Mahrani Rangkuty; Rusiadi Rusiadi; Saor Menanti Dolok Saribu (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
This research aims to see which variables, namely inflation, exchange rates, money supply, interest rates, and net exports, affect long-term combined share price fluctuations in five ASEAN countries, namely Indonesia, Malaysia, the Philippines, Singapore, and Thailand. Monetary policies of governments in countries have an important impact on how these countries manage their capital markets. This study uses secondary or time-series data from 1998 to 2018. With ARDL Panel, the result shows that in a panel variable the exchange rate is a leading indicator in ASEAN countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) but its position is not stable in the short run. Based on the overall results it is known that what is significant in the long term affects the fluctuation of the composite stock price index in ASEAN is the net export in the short term the exchange rate is significant in influencing the composite stock price index.